Effect of graphene doping on the charge carrier and thermoelectric properties of RCF-Bi2S3 composites - Jagadish P.R.; Khalid M.; Li L.P.; Amin N.; Walvekar R.; Chan A. (American Institute of Physics Inc., 2023)
Doping is a recognized way to modulate charge carrier properties for thermoelectric performance enhancement. Bismuth sulphide (Bi2S3) is a promising environmentally friendly alternative to toxic telluride based thermoelectric alloys, however its thermoelectric performance is limited by its poor electrical resistivity. In this paper, we report the effect of doping recycled carbon fibre (RCF)-Bi2S3 composite with graphene flakes and its corresponding effect on the charge carrier and thermoelectric properties. It is observed that the addition of graphene enhanced the power factor from 0.094?WK-2m-1 for RCF-Bi2S3 to 1.52?WK-2m-1 for 0.10 wt. %graphene doped RCF-Bi2S3. Doping Bi2S3 with graphene induced an energy filtering mechanism that allowed simultaneous modulation of decrease in electrical resistivity and an increase in Seebeck coefficient by 90 and 21% respectively. 2019 Author(s).